An Exploratory Study on the Köhler Effect and Flow in Long-term Exergaming. (October 2018) - Lee, Seungmin; Myers, Nicholas D.; Park, Taiwoo; Hill, Christopher R.; Feltz, Deborah L.
Background. One way to motivate people toexercise is to create a motivating social context, such as group exercise, due to social comparison opportunities. However, typical group exercise is not always easy for those who have problems in scheduling or social physique anxiety.Software-generated partners (SGPs) could offer a solution because they have advantages over human partners. Aim. This exploratory study examined thepsychological state of flow underKöhler paradigm over a 24-week exergame with different types of SGPs: Individual Control (IC), Always Superior Partner (AWS), and Not Always Superior Partner (NAS). Method. The experiment was a 3 (Type of the partner) × 3 (Time blocks) factorial design. Fifteen participants engaged in the experiment. A multivariate multiple regression with type of SGPs predicting flow state at the second and third block was conducted. Results. Participants with an NAS partner had significantly higher flow state, as compared to participants under IC, at both blocks. Participants with an AWS partner had approximately equal flow state, as compared to participants under IC, at both blocks. Conclusions. Possible reasons for flow perceptions with different types of SGPs over time were discussed in terms ofprogramming SGPs andflow theory .